THE EFFECT OF FACTORS LIQUIDITY, LEVERAGE, NPM, AND ROI ON CORPORATE VALUES (Study on Consumer Goods Companies Listed on Stock Indonesia Stock Period 2010-2013) - Timbuleng, Ferlen; Nangoy, Sientje C.; Saerang, Ivonne S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Analysis of the financial statements can help businesses, government and other users of financial statements in assessing a company's financial condition. The high value of the company will be followed by the high prosperity of shareholders, the higher the stock price the higher the value of the company. The purpose of this study was to examine the effect of liquidity, leverage, NPM, and ROI on corporate value of Consumer Goods companies listed on the Indonesia Stock Exchange period 2010-2013. Sample selection technique using purposive sampling and obtained eight companies as research samples. Method of this associative by using multiple linear regression techniques. The survey results revealed liquidity, leverage and ROI NPM have no significant negative effect on the value of the Company. For the investor should evaluate the company's financial ratios in advance if before want to invest in order to do the right investments and may reduce the risk. Keywords: liquidity, leverage, NPM, ROI, the value of the company